2001
DOI: 10.1177/1356336x010072002
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Issues in Adolescent Attitudes to Dance

Abstract: Qualitative research indicates that dance is an immensely popular recreational activity with young people, yet in many European schools it is often regarded as that aspect of the PE curriculum most suited to young children and high-school girls. This practice however is not based on empirical information; details relating to adolescent attitudes to dance for instance andhow these may vary with age and gender are sparse. Opinions were sought, therefore, from a total of 1668 11–16-year-old boys and girls, from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 31 publications
0
44
0
8
Order By: Relevance
“…This observation could be explained by a study of Passmore and French (2001), which revealed that women are more likely to actively engage in dance activities than men. Moreover, Sanderson (2001) suggested that this difference in attitude to dance is already established during childhood. In her study, opinions were sought from a total of 1,668 girls and boys, aged between 11 and 16 years, using questionnaires that included dance attitude scales.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be explained by a study of Passmore and French (2001), which revealed that women are more likely to actively engage in dance activities than men. Moreover, Sanderson (2001) suggested that this difference in attitude to dance is already established during childhood. In her study, opinions were sought from a total of 1,668 girls and boys, aged between 11 and 16 years, using questionnaires that included dance attitude scales.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes towards participation in dance practice within the social setting of PE vary between different age groups, between boys and girls as well as within groups of boys and girls (Lundvall & Meckbach, 2008;Redelius, 2004;Sanderson, 2001). Students have limited opportunities to learn and develop in the areas of aesthetical knowledge and experiences through dance (Gard, 2003(Gard, , 2006(Gard, , 2008Lundvall & Maivorsdotter, 2010;Sanderson, 1996Sanderson, , 2001) and whether or not they have the chance to do so often depends on teachers' competence and pedagogical knowledge (Goodwin, 2010; Swedish National Agency for Education [SNAE], 2005;Zavatto & Gabbei, 2008). Furthermore, folk dance practice in PE has strongly emphasised white dance forms (Rovengo & Gregg, 2007).…”
Section: Dance In Pementioning
confidence: 99%
“…Furthermore, folk dance practice in PE has strongly emphasised white dance forms (Rovengo & Gregg, 2007). Studies also show that only a small portion of PE classes has been devoted to dance and that dance has primarily been taught to younger children or girls (Carli, 2004;Sanderson, 1996Sanderson, , 2001.…”
Section: Dance In Pementioning
confidence: 99%
“…This knowledge is not based on empirical information such are very rare details relating to adolescent attitudes to dance, and how these may vary with age and gender are spares. According to model, established by [37] (Sanderson, P. 2001), with application of Dance Attitude Scales, recant studies were elaborated in Serbia, and region wider, with the basic aim to estimate assumed differences in attitudes to different dances with adolescents of both gender, and different age. The opinions on the variety aspects of dance art were sought, therefore from relative unified sub-samples of 11-15-year-old children (boys and girls), from particularly urban schools in Serbia (Niš, Kruševac, Valjevo, Jagodina, Vršac, Grocka), Bosnia and Herzegovina (Tuzla), and Montenegro (Podgorica, Danilovgrad) using questionnaires which included Likert-tipe dance attitudes scales on Art Dance, Social Dance and Folk dance [17], (Popovic, R., Djordjevic, I., Dolga, M., Purenovic, T., Pavlovic, M., 2009).…”
Section: Previous Researches Relative To Dance Studiesmentioning
confidence: 99%